-6x^2-17X+28=0

Simple and best practice solution for -6x^2-17X+28=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x^2-17X+28=0 equation:


Simplifying
-6x2 + -17X + 28 = 0

Reorder the terms:
28 + -17X + -6x2 = 0

Solving
28 + -17X + -6x2 = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -17X + -28 + -6x2 = 0 + -28

Reorder the terms:
28 + -28 + -17X + -6x2 = 0 + -28

Combine like terms: 28 + -28 = 0
0 + -17X + -6x2 = 0 + -28
-17X + -6x2 = 0 + -28

Combine like terms: 0 + -28 = -28
-17X + -6x2 = -28

Add '6x2' to each side of the equation.
-17X + -6x2 + 6x2 = -28 + 6x2

Combine like terms: -6x2 + 6x2 = 0
-17X + 0 = -28 + 6x2
-17X = -28 + 6x2

Divide each side by '-17'.
X = 1.647058824 + -0.3529411765x2

Simplifying
X = 1.647058824 + -0.3529411765x2

See similar equations:

| 4x+7=3x-1 | | 13x-147=6x-14 | | 57-2x=7x+23 | | 7-9x=36-13x | | 6x+9=-17-7x | | -7x^2+52x-85=0 | | -x^2-4X=0 | | .6(d+3)=3d | | -x^2-3x+18=0 | | -x^2-4x-3=0 | | 7x-9=15+4x | | x^2+12x+33=0 | | 9a-7+a=14+3a | | 6y+12-9=15 | | 4b+2b=3b+36 | | 7x^2+38x+15=0 | | -x^2-9x-18=0 | | 9x-6x+2=23 | | 2x^2-3x-12=0d | | 5x^2-23x+24=0 | | 2x+3(1-2x)=3x-2 | | 3(2x+4)=4x+20 | | n^2+2n+93=0 | | 15+26x=-8x^2 | | 12(x+3)=4(3x+4)+20 | | n^2-4n+5=8 | | 0.30(6)+0.05x=0.15(12+x) | | 3x-4=-x+12 | | 15x+10-2x+12=15 | | 10x+x=3+x | | 11x-4(x-2)=7x+4 | | -(6y+4)-(-5y-5)=-3 |

Equations solver categories